Identification of Known and Novel MicroRNAs in Raspberry Organs Through High-Throughput Sequencing - Yan, Gengxuan; Zhang, Jie; Jiang, Meng; Gao, Xince; Yang, Hongyi; Li, Lili (Frontiers in Plant Science, 2020)
MicroRNAs (miRNAs) are a class of small endogenous RNAs that play important regulatory roles in plants by negatively affecting gene expression. Studies of miRNAson the identification of miRNAs and their functions in various plant species and organs have been a very important direction in contributed significantly contributed to plant development research. In the current study, we utilized high-throughput sequencing technology to revealdetect the miRNAs in the root, stem, and leaf tissues of raspberry (Rubus idaeus) root, stem, and leaf.). A total of more than 35 million small RNA reads with sizes ranging in size from 18 to 35 nucleotides were obtained, whilewith 613 147 known miRNAs and 1,417542 novel miRNAs were identified among the three organs. Sequence verification and the relative expression profiles of the fivesix known miRNAs were constructedinvestigated by stem-loop qRT-quantitative real-time PCR. Furthermore, the potential target genes of the known and novel miRNAs were predicted and subjected to Gene Ontology (GO) and KEGGKyoto Encyclopedia of Genes and Genomes pathway annotation. Enrichment analysis of the GO-representedassociated biological processes and molecular functions revealed that these target genes were potentially involved in a wide range of metabolic pathways and developmental processes. Moreover, the miRNA target prediction revealed that most of the targets predicted as transcription factor -coding genes are involved in cellular and metabolic processes. This studyreport is the first report on miRNA identification to identify miRNAs in the raspberry. We analyzed the The detected miRNAs were analyzed by cluster analysis according to their expression, and predictedwhich revealed that thethese conservative miRNAs are necessary for plants.plant functioning. The results add a large quantity of novel miRNAs to the raspberry transcriptome, providing a useful resource for the further elucidation of the functional roles of miRNAs in raspberry growth and development.